Impact of wheat flour varieties on the life history and demographic parameters of red flour beetle, Tribolium castaneum Herbst. Issue 4 (2nd October 2019) - Maroufpoor, Mostafa; Ebadollahi, Asgar; Ullah, Mohammad Shaef
Abstract: Red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) is a cosmopolitan pest of stored grains, and the most important insect pests in grain processing and other storage facilities. The current study is designed to characterize the life history parameters of T. castaneum such as egg-to-adult development, reproduction, male and female longevity on three conventional wheat flour varieties, i.e., Azar 2, Homa and Sardari. Adult pre-oviposition and oviposition periods were significantly higher for females reared on Azar 2 variety compared to Homa and Sardari varieties. Although total fecundity of T. castaneum female reared on three flour varieties were not significantly different, daily fecundity was higher on Homa than Azar 2 and Sardari varieties. The intrinsic rate of natural increase varied from 0.0074 to 0.0173 day −1 on flour varieties. The mean generation time ( T ) of T. castaneum were considerably affected by flour varieties. Based on results of the present study, Sardari is a less favorable variety for the development and reproduction of T . castaneum and may be considered for management of this detrimental pest.